Negligible local-factor influences on tree ring cellulose δ18O of Qilian juniper in the Animaqing Mountains of the eastern Tibetan Plateau - Chenxi Xu (Tellus: Series B, Chemical and Physical Meteorology, 2017)
Tree ring cellulose oxygen isotopes (δ18O) were measured on 21 trees of Qilian juniper from the Animaqing Mountains, Tibetan Plateau, to investigate intra- and inter-tree variability, potential juvenile and elevation effects and climatic implications. There are no significant differences in mean and standard deviation of tree ring δ18O values at different heights in individual trees. Tree ring δ18O values from different directions show a high degree of coherence. The mean and standard deviation for vertical and circumferential δ18O time series are very similar, and δ18O data from different heights and directions are highly correlated (r > 0.88). The δ18O values of young trees are lower than those of old trees in the first 10 years of tree growth. Tree ring δ18O data from five different altitudes are highly correlated (r > 0.88) and share similar climatic signals. As such, an altitude effect on tree ring δ18O is not observed. Our results indicate that samples from one site, regardless of sampling height, direction or altitude, can be used to reconstruct a long-term δ18O record. Tree ring δ18O data from the Animaqing Mountains show a significant negative correlation (r = −0.67; p < 0.001) with May–July regional precipitation and appear to be a promising proxy for precipitation reconstruction.